Agnathia holoprosencephaly complex: case report. - Suárez Obando, Fernando; Prieto, Juan Carlos (Colombia Medica, 2007)
A case report of the agnathia holoprosencephaly complex and a review of the literature related to the complex genetic and embryologic aetiology of this group of major birth defects of face and central nervous system are informed. The present clinical case is the first reported in Colombia.